The Importance of Community-Based Media for Building and Sustaining Lesbian Subcultures: The Role of Montréal’s Dykes on Mykes Radio Show - MacPhee, Marie-Claire; Hogan, Mél (Global Media Journal, 2006)
This paper was originally written for and presented at the Lesbian Lives XIII: Historicizing the Lesbian Conference in Dublin, Ireland in February 2006. The essay considers the history of Dykes on Mykes, a groundbreaking, lesbian and queer community-based radio program in Montréal, Canada. The authors, who are the show’s current hosts and technicians, collected data by examining the show’s archives and conducting individual and focus group interviews with Dykes on Mykes’ past and present hosts. These data reveal that changes in Dykes on Mykes’ programming and foci correlate closely with contemporary cultural and social developments among lesbian communities in Montréal.